2019
DOI: 10.3390/su11092622
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impact of Socioeconomic Forces and Policy Implications: Spatial-Temporal Dynamics of the Ecosystem Services Value in Yangtze River Delta, China

Abstract: Water can carry or overturn a boat. Natural resources form the foundation of human survival and development. However, land use change caused by human urban civilization has damaged the natural environment and in turn threatened the continuation of human civilization. Accordingly, it is crucial to analyze the impacts of human activities on land use change and consequent dynamics of ecosystem service value (ESV). For the sustainable development of human beings, an investigation should be conducted to explore wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 93 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…For instance, Wang's study identified the positive effects exerted by the proportion of renters, the floating population, wage levels, the cost of land, the housing market and city service levels on housing prices, and the negative influence exerted by living space by using these conventional spatial regression techniques (including SLM and SEM) [88]. Chen confirmed that population growth and economic advancement exerted a considerable influence on socioeconomic development, thereby affecting the change of ecosystem service value (ESV) based on the study of the impact of human activities on land use change and consequent dynamics of ESV by using spatial lag and spatial error models [130]. Furthermore, Zhang suggested that all air pollution emissions in China's 31 provinces had significant spatial dependence and strong spillover effects at different significance levels by using spatial lag models [131].…”
Section: Mechanism Explaining the High-vs Low-skilled Gap In Spatialmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, Wang's study identified the positive effects exerted by the proportion of renters, the floating population, wage levels, the cost of land, the housing market and city service levels on housing prices, and the negative influence exerted by living space by using these conventional spatial regression techniques (including SLM and SEM) [88]. Chen confirmed that population growth and economic advancement exerted a considerable influence on socioeconomic development, thereby affecting the change of ecosystem service value (ESV) based on the study of the impact of human activities on land use change and consequent dynamics of ESV by using spatial lag and spatial error models [130]. Furthermore, Zhang suggested that all air pollution emissions in China's 31 provinces had significant spatial dependence and strong spillover effects at different significance levels by using spatial lag models [131].…”
Section: Mechanism Explaining the High-vs Low-skilled Gap In Spatialmentioning
confidence: 86%
“…Furthermore, Zhang suggested that all air pollution emissions in China's 31 provinces had significant spatial dependence and strong spillover effects at different significance levels by using spatial lag models [131]. Given that many scholars conduct the similar research on migration, housing prices, and other socioeconomic problems based on these conventional spatial regression models [88,130,131], we also choose the ordinary least square (OLS), the spatial lag (SLM) and the spatial error (SEM) models in this study to look into migrant rent affordable stress issues in urban China. In this paper, we analyze the driving factors that can interpret the variance of the high-and low-skilled migrants in terms of the geographic distribution of high-rent-stress samples (rent-income ratios above 25 percent), by using the ordinary least square (OLS), the spatial lag (SLM) and the spatial error (SEM) models.…”
Section: Mechanism Explaining the High-vs Low-skilled Gap In Spatialmentioning
confidence: 99%
“…Studies have shown that in order to pursue foreign investment, local governments even adjust their planning without limit to meet the demand for land development [63,64]. Moreover, in a top-down planning system, the development orientation and function of each town are different, thus forming different town rank that can affect the input of the above factors and directly affect the expansion of built-up land that determine the outcomes of plan implementation [65]. To this end, we select the potential impact factors, including the population density (PD), the rate of urbanisation (URB), the gross domestic product (GDP), the fiscal revenue (FR), the fixed assets investments (FAI), and the rank of town (RT).…”
Section: Potential Influencing Factorsmentioning
confidence: 99%
“…Moreover, the rank of town reflects the importance of the economic development of each township within a county. If the township is on a higher rank which is given by national economic and social development planning, it will get more investment from the upper government that more infrastructure projects and investment will be prioritized located in these townships [65]. It also means that planning is more likely to face the situation that development needs and land development requirements is out of expected.…”
Section: Economic Development Brings Significant Uncertainty To the Imentioning
confidence: 99%
“…However, previous studies have shown that changes in ESVs are the result of a combination of multiple driving factors. Therefore, a comprehensive analysis of the impact of natural factors [ 46 , 47 , 48 , 49 ], socio-economic factors [ 49 , 50 , 51 ], and political factors [ 44 , 52 ] on the ESVs is helpful to understand the ecological environment protection and formation mechanism.…”
Section: Introductionmentioning
confidence: 99%